Pediatric Hemoptysis - Hana Khairina Putri Faisal; Faisal Yunus; Nastiti Rahajoe (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Hemoptysis or expectoration of blood is one of the respiratory symptoms in children, hemoptysis is hard to detect because it is often swallowed. The common causes of hemoptysis in adults include bronchiectasis, tuberculosis, pulmonary mycosis, and lung cancer. On the other hand, hemoptysis in children is often caused by tracheobronchitis, pneumonia, bronchiectasis in cystic fibrosis, and foreign body aspiration. Bleeding of the pulmonary artery or bronchial artery is the cause of hemoptysis. Upper airway examination is important to rule out epistaxis as the cause of hemoptysis. The primary objectives of hemoptysis management are asphyxia management, bleeding cessation, and treatment of the underlying disease. When all other treatments fail to stop the bleeding, surgery is recommended.